2008
DOI: 10.1074/jbc.m707269200
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Calcium-sensing Receptor Activation Induces Vitamin D Receptor Levels in Proximal Kidney HK-2G Cells by a Mechanism That Requires Phosphorylation of p38α MAPK

Abstract: 2؉ ] e concentration in the physiological range is capable of directly increasing renal proximal VDR expression, and the induction mechanism requires activation of the CaSR and signal mediation by the p38␣ MAP kinase pathway.Extracellular ionized calcium [Ca 2ϩ ] e is a critical mediator of cell signaling for the storage and release of both parathyroid hormone (PTH) 2 and calcitonin. Homeostasis of [Ca 2ϩ ] e is important to proper neuromuscular contractions, cellular integrity, and the deposition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 66 publications
(58 reference statements)
1
23
0
Order By: Relevance
“…However, components of the signaling pathway that lie between the Ca 2ϩ /CaMKII signaling and the cell cycle machinery have been undefined. This is particularly relevant, since potential connections between Ca 2ϩ /CaMKII signaling and multiple signaling pathways have been reported in many cell types; elevated extracellular Ca 2ϩ can activate the MAPK pathways (12), the CaMKII-MAPK pathways regulate the neuronal cell fate determination (13), and the Wnt-5a-mediated Ca 2ϩ signaling activates the TAK1-NLK pathway via CaMKII (14). Our results also show that hCaMKIIN␣ deactivates MEK/ ERK and causes the inhibition of S-phase progression of the cell cycle (11).…”
mentioning
confidence: 99%
“…However, components of the signaling pathway that lie between the Ca 2ϩ /CaMKII signaling and the cell cycle machinery have been undefined. This is particularly relevant, since potential connections between Ca 2ϩ /CaMKII signaling and multiple signaling pathways have been reported in many cell types; elevated extracellular Ca 2ϩ can activate the MAPK pathways (12), the CaMKII-MAPK pathways regulate the neuronal cell fate determination (13), and the Wnt-5a-mediated Ca 2ϩ signaling activates the TAK1-NLK pathway via CaMKII (14). Our results also show that hCaMKIIN␣ deactivates MEK/ ERK and causes the inhibition of S-phase progression of the cell cycle (11).…”
mentioning
confidence: 99%
“…As is the case for other GPCRs, the activated CaR is capable of activating multiple types of G proteins from different G protein subfamilies, primarily G␣ q/11 and G␣ i . This leads to a range of cellular responses, including stimulation of phospholipase C␤ (PLC␤), production of inositol 1,4,5-triphosphate (IP 3 ), release of intracellular Ca 2ϩ (Ca 2ϩ i ), stimulation of mitogen-activated protein kinases (MAPKs), and an inhibition of adenylate cyclase, causing a decrease in cAMP levels (Brown and MacLeod, 2001;Maiti et al, 2008) (Fig. 1).…”
mentioning
confidence: 99%
“…P38 is one of several MAPKs activated by the CaSR in various cell types. Since knocking down the CaSR with siRNA prevented the high Ca 2þ o -evoked increase in VDR expression, the latter was CaSR-mediated [92]. The use of siRNA to prove the CaSR's role in the concomitant inhibition of the expression of CYP27B1 was not reported [90].…”
Section: The Casr and Regulation Of 1-hydroxylation Of 25-hydroxyvitamentioning
confidence: 91%
“…Maiti and Beckman used a proximal tubular cell line, HK-2G, in which they had shown that high extracellular calcium inhibits the expression of CYP27B1 [90], to demonstrate that high Ca 2þ o up-regulates the expression of the VDR [24]. This effect was mediated by a p38 mitogen-activated protein kinase (MAPK)-dependent mechanism [92]. P38 is one of several MAPKs activated by the CaSR in various cell types.…”
Section: The Casr and Regulation Of 1-hydroxylation Of 25-hydroxyvitamentioning
confidence: 98%